Arctic Flora and Fauna: Recommendations for Conservation - Conservation of Arctic Flora and Fauna (CAFF) (CAFF, 2001)
Project outline of CAFF's Arctic Flora and Fauna: Recommendations for Conservation, including key considerations, conservation issues and opportunities.